2015
DOI: 10.1097/tp.0000000000000664
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Stromal Fiber ER-TR7 Modulates CD4+ T Cell Lymph Node Trafficking and Transplant Tolerance

Abstract: Background Trafficking and differentiation of naïve CD4+ and regulatory T cells (Treg) within the lymph node (LN) are integral for tolerance induction. The LN is comprised of stromal fibers that dictate lymphocyte migration and LN structure, organization, and microanatomic domains. Distribution of the stromal fiber ER-TR7 changes within the LN following antigenic challenge, but the contributions of ER-TR7 to the resulting immune response remain undefined. We hypothesized that these stromal fiber structural cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 41 publications
(62 reference statements)
0
34
0
Order By: Relevance
“…These fibers and networks not only help in the migration of T cells, B cells and APCs; but also provide a platform for cognate interactions which play important roles in shaping immunity and tolerance [49]. Reagents that disrupt the stromal fiber network prevent the generation and maintenance of transplantation tolerance [50,51]. Our present results showed that B cell depletion alters the migration and distribution of Tfh and Tfr in specific cellular compartments of the secondary lymphoid organs.…”
Section: Discussionmentioning
confidence: 70%
“…These fibers and networks not only help in the migration of T cells, B cells and APCs; but also provide a platform for cognate interactions which play important roles in shaping immunity and tolerance [49]. Reagents that disrupt the stromal fiber network prevent the generation and maintenance of transplantation tolerance [50,51]. Our present results showed that B cell depletion alters the migration and distribution of Tfh and Tfr in specific cellular compartments of the secondary lymphoid organs.…”
Section: Discussionmentioning
confidence: 70%
“…96 Tregs are recruited around the HEV and CR under tolerogenic compared to immune conditions. 96 Tregs are recruited around the HEV and CR under tolerogenic compared to immune conditions.…”
Section: Blood Endothelial Cells In Tolerancementioning
confidence: 99%
“…96,[113][114][115] Laminin 411 and 511 serve as coinhibitory and costimulatory li- Laminin α4 is associated with tolerance and laminin α5 is associated with immunity. Laminin α4 increases in response to tolerance induction, increasing the laminin α4:α5 ratio.…”
Section: Lymph Node Microenvironment: Stromal Fibers and Conduitsmentioning
confidence: 99%
See 2 more Smart Citations